2010
DOI: 10.1590/s1415-47572010005000004
|View full text |Cite
|
Sign up to set email alerts
|

Immediate response of myocardium to pressure overload includes transient regulation of genes associated with mitochondrial bioenergetics and calcium availability

Abstract: Ventricular hypertrophy is one of the major myocardial responses to pressure overload (PO). Most studies on early myocardial response focus on the days or even weeks after induction of hypertrophic stimuli. Since mechanotransduction pathways are immediately activated in hearts undergoing increased work load, it is reasonable to infer that the myocardial gene program may be regulated in the first few hours. In the present study, we monitored the expression of some genes previously described in the context of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This discrepancy might be explained by incomplete inhibition of G␣ 13 -mediated signaling in p115-RGS transgenic mice, for example, resulting from the fact that the ␣MHC promoter driving expression of the inhibitory peptide is downregulated as early as 6 hours after the onset of pressure overload. 34 In addition, the ␣MHC promoter is active already during embryogenesis, potentially causing developmental defects and/or complex compensatory responses. In our model of tamoxifen-inducible Cre-mediated .…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might be explained by incomplete inhibition of G␣ 13 -mediated signaling in p115-RGS transgenic mice, for example, resulting from the fact that the ␣MHC promoter driving expression of the inhibitory peptide is downregulated as early as 6 hours after the onset of pressure overload. 34 In addition, the ␣MHC promoter is active already during embryogenesis, potentially causing developmental defects and/or complex compensatory responses. In our model of tamoxifen-inducible Cre-mediated .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these studies, we observed that 1 week was sufficient to induce hypertrophy using similarly sized needles for ligation. A separate report [ 27 ] documented changes in LV weight to body weight ratio from one hour to 48 hours post-operation. In the initial 48 hours, no significant change was detected, consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%